SECRETORY CARCINOMA OF SALIVARY GLAND: A CLINCOPATHOLOGICAL ANALYSIS - Akhtar, Noreen; Atiq, Aribah; Loya, Asif; Hassan, Usman; Hussain, Mudassir; Abu-Bakar, Muhammad; Mushtaq, Sajid (Journal of Ayub Medical College Abbottabad, 2020)
Background: Secretory carcinoma of the salivary gland (SC) is a new entity that harbours a specific ETV6 gene rearrangement. The clinical behaviour of this tumour is not well-known as it is a relatively new entity but it is generally considered as a tumour of low malignant potential. The objective of the study was to find out the frequency of ETV6 translocation in cases diagnosed based on histology and immunohistochemistry, to study morphological features and immunohistochemical findings of our cases and to determine the survival and disease-free status of our patients. Methods: Twenty-five diagnosed cases of SC were retrieved from the archives of SKMCH and RC. Diagnosis was made primarily based on morphology and immunohistochemistry. Immunohistochemistry includes S100, p63, mammaglobin, DOG 1, GCDFP-15, TTF-1, GATA3, SMA, AMA, and AR. The diagnosis was further confirmed by molecular testing, i.e., Fluorescence in situ hybridization (FISH) studies to observe specific ETV6 gene break. Follow up of the patients was done by developing a questionnaire. Statistical analysis of the data was done using SPSS-23.0. Results: The mean age of diagnosis was 41±17.4 and the male to female ratio was 1.5:15. The mean size of the tumour was 45.48±27.35. The most common site of the tumour was parotid gland (60%). On morphology, SC showed a wide range of morphological patterns, most common being the tubular, microcystic, intraductal, and papillary. Immunohistochemical stains mammaglobin (22/22), GCDFP-15(15/15) and GATA3 (10/10) showed 100% positive result. However, all cases were negative for p63 (0/18) and DOG 1(0/11). ETV6 break was seen in 17/17 cases (100%). The mean disease-free survival was 75 months and the overall survival was 51.90±2.80 months. Conclusion: This study highlights the presence of specific molecular alteration in all cases, which were diagnosed based on morphology and immunohistochemistry. Keywords: Secretory carcinoma of Salivary gland; ETV6